SHORT AND MIDTERM OUTCOME OF FALLOT'S TETRALOGY REPAIR IN INFANCY: A SINGLE CENTER EXPERIENCE IN A DEVELOPING COUNTRY - Memon, Muhammad Kamran Younis; Akhtar, Saleem; Mohsin, Muhammad; Ahmad, Waris; Arshad, Aleena; Ahmed, Mehnaz Atiq (Journal of Ayub Medical College Abbottabad, 2019)
Background: Primary repair of ToF between 3-12 months is the preferred mode of treatment worldwide, with low surgical mortality. This study reviews our experience of ToF repair in infancy and its short and midterm outcomes in a single centre from a developing country. Methods: Data of all patients with Tetralogy of Fallot repair during infancy from January 2007 to Feb 2018 was reviewed. Preoperative, operative, and postoperative data was analysed. Outcome of the infants was assessed through discharge/death, low cardiac output syndrome (LCOS), prolonged intubation, duration of cardiac intensive care unit (CICU) and hospital stay. Results: Forty-four patients who underwent TOF repair in infancy during this period were included. The mean age and weight were 9.39±2.32 and 7.20±1.30 respectively, 77.3% (34 patients) were male, 68.18% (30 patients) had saturation >75%. Mean intubation period was 4.05±6.58 days, 12 (27.3%) patients developed LCOS, mean cardiopulmonary bypass (CPB) time, aortic cross clamp (ACC) time and ionotropic score were 133.52±62.4, 98.66±58.62 and 33.27±71.13 respectively. Mean CICU and hospital stay was 6.60±7.18 and 12.05±7.74 respectively. Five (11.3%) patients expired in postoperative period. Baseline saturation ‰¤75% is independent risk factor for LCOS and prolong intubation period. In the last six years our mortality decreased to 8% from 15.7% during the previous six years, while our mean intubation duration, CPB time, ACC, hospital stay and CICU stay have all shown improvement. Conclusion: TOF repair during infancy is safe procedure in expert hands with acceptable morbidity and mortality. Baseline saturation ‰¤75% is independent risk factor for LCOS and prolonged intubation period. Last six years have shown considerable improvement in our surgical morbidity and mortality due to improvement in surgical expertise. Keywords: Tetralogy of Fallot repair; Low cardiac output syndrome; Congenital heart disease surgery; Operative mortality ToF